2015
DOI: 10.1513/annalsats.201411-504oc
|View full text |Cite
|
Sign up to set email alerts
|

Post–Acute Care Use and Hospital Readmission after Sepsis

Abstract: Rationale: The epidemiology of post-acute care use and hospital readmission after sepsis remains largely unknown.Objectives: To examine the rate of post-acute care use and hospital readmission after sepsis and to examine risk factors and outcomes for hospital readmissions after sepsis. Methods:In an observational cohort study conducted in an academic health care system (2010-2012), we compared post-acute care use at discharge and hospital readmission after 3,620 sepsis hospitalizations with 108,958 nonsepsis h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
101
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 53 publications
13
101
0
1
Order By: Relevance
“…The target population included survivors with a MICU length of stay of at least 2 days who were not discharged to hospice. Eligible subjects were identified using a previously validated administrative clinical database (20). The study was reviewed and approved by the institutional review board with the use of verbal informed consent (protocol #820066).…”
Section: Methods Study Design and Populationmentioning
confidence: 99%
“…The target population included survivors with a MICU length of stay of at least 2 days who were not discharged to hospice. Eligible subjects were identified using a previously validated administrative clinical database (20). The study was reviewed and approved by the institutional review board with the use of verbal informed consent (protocol #820066).…”
Section: Methods Study Design and Populationmentioning
confidence: 99%
“…(9) A growing body of literature describes hospital readmissions after initial treatment for severe sepsis. (6, 7, 1012) Sepsis readmissions are important not only because of the potential financial implications, but also because these events may signify shortcomings in initial inpatient treatment or follow-up outpatient care. Studies of community medical centers and samples of tertiary care hospitals have identified increased short- and long-term readmission rates among patients discharged after treatment for sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of community medical centers and samples of tertiary care hospitals have identified increased short- and long-term readmission rates among patients discharged after treatment for sepsis. (6, 7, 10, 11) However, there are no national data describing hospital readmissions after severe sepsis. Furthermore, few studies have focused on very early severe sepsis readmissions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A maioria das mortes ocorreu nos primeiros seis meses, mas o risco permaneceu elevado aos dois anos. Após a alta do hospital, a sepse comporta um maior risco de morte (até 20%), bem como um risco aumentado de sepse adicional e internações hospitalares recorrentes (até 10% são readmitidos) (15)(16)(31)(32) . …”
Section: Discussionunclassified